Financial Conflicts of Interest in Inflammatory Bowel Disease Guidelines. Issue 4 (5th October 2018) - Grindal, Alexander W; Khan, Rishad; Scaffidi, Michael A; Rumman, Amir; Grover, Samir C
Abstract: Background: Industry payments can lead to financial conflicts of interest (FCOI) among authors of clinical practice guidelines (CPGs). Guidelines for inflammatory bowel disease (IBD) may be at particularly high risk. We determined the prevalence of FCOI in IBD CPGs produced by various gastroenterology societies. Methods: We conducted a cross-sectional analysis of FCOI disclosure among CPGs related to the management of IBD. We ascertained the prevalence and types of FCOI for each guideline and determined adherence to National Academy of Medicine (NAM) standards. FCOI disclosures were compared between societies producing CPGs. Results: We identified 11 relevant CPGs with 173 total authors. There were 117 (68%) authors who declared a payment. A total of 107 (62%) authors declared FCOI related to a medication recommended in the guideline. There was a significant difference ( P < 0.001) between the proportion of authors with FCOI between countries or regions. Authors of US CPGs had a significantly lower FCOI prevalence (19%) compared with other societies. Authors of UK CPGs had a significantly lower FCOI prevalence (56%) compared with Canadian (84%) and European (94%) CPGs. Three (27%) guidelines adhered to both NAM standards. Conclusions: A substantial portion of authors of IBD CPGs had FCOI. Our study found a significant difference in FCOI prevalence based on CPG sponsor nationality. Most CPGs for IBD did not adhere to NAM standards for FCOI disclosure.